Regulating European Union’s Border in Africa: The Practice of Semi-permeable Border in Ceuta and Melilla - Rahmadan, Yanuar (Nation State: Journal of International Studies, 2024)
Ceuta and Melilla are two enclaves that belong to Spain in Morocco and have become the contact points of the irregular migrants coming from Africa that are attempting to reach the European continent. The enclaves have utilized innovative technology and barbed wire, but immigrant crises have occurred over the years. Despite the crises, the Spanish and Moroccan governments choose to perform a semi-permeable border. This article explains the semi-permeable border using the liberal institutional theory. This article argues that a semi-permeable border is chosen by the Spanish and Moroccan governments to fulfill their mutual self-interests. The Spanish government agrees to perform a semi-permeable border to retain the symbolic border of the region. The blurring overlap in the enclaves has put the Spanish government to use help from the European Union to conduct security measures in the region. The Moroccan government agrees to perform a semi-permeable border to retain its influence over the enclaves and uses the immigrant crises as a bargaining chip for the European Union. The European Union maximizes the performance of a semi-permeable border to pursue its interest, which is to conduct the Euro-Mediterranean Free Trade Agreement.